Between tradition and innovation: the use of textbooks and didactic digital contents in classrooms - Alessandra Anichini; Laura Parigi; Stefania Chipa (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2017)
Since 2013, the Italian Minister of Education promoted the use of digital or mixed paper-digital texts in the classroom by means of legislative act (Lex 128/2013). Since then, adoption of the textbook is not mandatory in our country: Italian schools, according to their autonomy, can choose to adopt teaching materials from publishers, Open Educational Resources, or auto-produced texts. The law legitimates the experience of some Italian schools that are innovating the use of textbooks and are involved in a process of auto-production of content (textbooks or DDC, Didactic Digital Content). The article attempts to describe the work of these schools within a network of practice named «Avanguardie Educative». It intends to analyse teachers beliefs and attitudes upon «studying», «textbooks» and «digital texts», to capture innovative aspects, but also to look at difficulties and obstacles along the path of innovation, not always so clear and well defined.